A Mulher e/em seu tempo: um estudo de Cláudia na década de 1960 (1961-1969) - Portilho, Raquel de Souza Moreira (2010)
The 1960s is an important period for Brazil and the world. During these years events such as the Cold War, intense social mobilizations (from country to urban workers), military coups and revolutions took place. Claudia, Brazil s first major women s magazine, was created in 1961 and under these conditions had, also, to handle the explosion of the second phase of feminism, which, as a result, brought several protests from women and consequently, from its readers. This paper has proposed, from the exhibition of historical contexts of the 1960s and the moments of feminist agitation, to combine those thoughts with the ideas of identity, representation and gender to research the pages of Claudia during that period. In parallel, we examined the trajectory of women press, with the intention of showing how this thread has developed over the centuries, contributing to the creation of Claudia, in addition to examining the precepts that make the women press a journalistic practice, compared with the journalism of reference", meaning that the differences between them are the result, especially, of a hierarchy between public and private, or yet, between male and female. The research of Claudia during the 1960s showed that the magazine was in constant clash when it comes to the two propositions quoted above: it was possible to find not infrequently in the pages of the magazine placements in which the magazine would place itself as a publication dedicated to women - with all its remarkable characteristics, and would also claim itself as a serious journalistic vehicle, which based its editorial on the principles of journalism of reference . This tension between public and private is also reflected in the content of Claudia: a possible identity of woman was constantly proposed and reproduced by the magazine, but it was far from being homogeneous. We believe that the tensions generated by the events in the 60s have contributed definitively to how Claudia addressed most of its issues.